Mahesh Datani’S Dance As Being a Person As a Possible Legendary Theatre: Exploring the fusion of Western and Indian theatrical techniques in Mahesh Dattani's plays (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Mahesh Dattani, a legitimate contemporary voice, a head,writer, maker, organizer of a theatre aggregate regarded as "Playpen"is a cannily fortifying Sahitya Academy Winner with an superb familiarity withIndian theatre. There is fitting mixing of Western educated awareness andIndian showy strategies in his plays. He himself remarks on the pertinence ofIndian theatre: